Gestión de control de los inventarios para la optimización de la rentabilidad en las empresas del sector ferretero - Tubay Lino, Glenda Maricela (2021)
The inventory system corresponds to an issue that needs to be addressed to improve their control and determine how companies dispose and record their merchandise in terms of the different techniques known in accounting theory, in the same way, it is It is necessary to generate a practical vision regarding inventory management, which can serve as a valid scientific exercise that results in a relevant technical report that serves as a model for future researchers and auditors. The research presented has the general objective of analyzing the behavior of inventory control management and its impact on the profitability of the hardware sector in the city of Guayaquil. The methodology to achieve this objective was with a descriptive research that also contains a quantitative and qualitative approach due to convenience sampling that will be used through three research instruments such as the survey, the interview and the documentary analysis of the financial statements……………